:)

🙂

  • log(3x-5)=-1;

    3x-5=2;

    3x=7;

    x=7/3.

    log(2x-1)=log(x+x-3);

    2x-1=x+x-3;

    x-x-2=0;

    x=-1; — решение C;

    x=2.

    log(x)+log(x-6)=2;

    log(x-6x)=2;

    x-6x=0,25;

    x-6x-0,25=0;

    d=37… Дальше дорешай.

    log(5x-1)>log(2-3x);

    5x-1>2-3x;

    8x>3;

    x>3/8.

    log(2x-1)(1/2);

    2x-12;

    2×3;

    x1,5.

  • 1) (1/2)^(-1)=3x-5

    3x-5=2

    3x=5+2

    3x=7

    x=7/3

    2) 2x-1=x^2+x-3

    x^2-x-2=0

    D=9

    x=-1

    x=2

    4) 4^(1/2)2x-1

    22x-1

    2x-12

    x1.5

    5) 5x-1>2-3x

    8x>3

    x>3/8